The natural history collections of Adam Mickiewicz University in Poznań (Poland): an outline of their history and content - Jackowiak, Bogdan; Błoszyk, Jerzy; Celka, Zbigniew; Konwerski, Szymon; Szkudlarz, Piotr; Wiland-Szymańska, Justyna (Biodiversity: Research and Conservation, 2022)
The origins of scientific nature collections in Wielkopolska (Western Poland) date back to the seventeenth century. Their development was repeatedly disrupted by major events, including two world wars fought in Poland in the twentieth century. The rescued historical collections as well as specimens of algae, plants, fungi and animals systematically collected after 1945 are now stored under optimal conditions at the Faculty of Biology of Adam Mickiewicz University in Poznań (FBAMU). The current collections include approximately 2.2 million pre-catalogued objects that document not only the biodiversity of Wielkopolska and Poland but also that of many regions of the world on all continents. Specimens included in the FBAMU are used extensively in taxonomic, biogeographic, phylogenetic, ecological and genetic studies. The collections also have significant educational value and help disseminate knowledge about biodiversity.